2021
DOI: 10.24052/ijbed/v09n01/art-02
|View full text |Cite
|
Sign up to set email alerts
|

Insights from behavioural economics to enhance the environmental dimension of sustainable development

Abstract: Individuals everywhere and every day take decisions and make choices that affect the environment either positively or negatively. By understanding and analysing the determinants and incentives of humans' decision-making process, behavioural economics helps change behaviours toward more sustainable practices using efficient and well- designed policies. Using a survey targeting 4000 households' participants from 11 Egyptian governorates in 2019, the paper explores attitudes' determinants and behaviour's motivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Moreover, Ismail & AbdElkhalek (2021) revealed that behavioural economics plays a minimal role in developing sustainable development policies and environmental interventions in Egypt, which is a developing country, and a general willingness to change one's way of thinking towards more environmentally friendly choices, particularly if policy interventions derive the behaviours in that direction.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Ismail & AbdElkhalek (2021) revealed that behavioural economics plays a minimal role in developing sustainable development policies and environmental interventions in Egypt, which is a developing country, and a general willingness to change one's way of thinking towards more environmentally friendly choices, particularly if policy interventions derive the behaviours in that direction.…”
Section: Discussionmentioning
confidence: 99%